Delay among women reporting symptoms of Breast cancer - PBVR Kumari; CSE Goonewardena (College of Community Physicians of Sri Lanka, 2011)
Objective To describe factors related to timing of first contact with an allopathic medical practitioner, among patients with symptoms of breast cancer attending breast clinic at Cancer Institute, Maharagama. Method A descriptive cross sectional study was conducted among a total of 335 consecutive women who attended the clinic for the first time, during the period of survey. All the patients registered at the breast clinic for the first time were recruited. A pre-tested, interviewer administered questionnaire was used. Results Thirty eight percent (n=127) of patients had a delay in presentation which was defined as greater than 12 weeks. The mean time duration between experiencing a symptom and in seeking medical care was 11.5 weeks (SD=1.41). Factors significantly related to delayed presentation were age (elderly) [p<0.001], marital status (unmarried, divorced or widowed) [p=0.037], fertility status (women with no children) [p=0.011], ethnicity (Tamils and Muslims) [p= 0.002], an income of less than Rs. 10,000 (p= 0.002), low social class (p<0.001), first symptom not being a lump (p<0.001), a distance of > 5 km from home to medical facility (p=0.003), not attending a well woman clinic (p=0.002), assuming the condition to be a benign one (p<0.001), having undergone any kind of surgery under general anaesthesia (p =0.038) and poor knowledge on breast cancer (p<0.001). Conclusion Delay in seeking treatment for suspected breast cancer is a problem in Sri Lanka. Women may benefit from greater awareness of the benefits of early detection and expansion of diagnostic and treatment facilities for breast cancer. Key words: Breast cancer; Symptom; Delay DOI: http://dx.doi.org/10.4038/jccpsl.v16i1.3867   Journal of the College of Community Physicians of Sri Lanka Vol.16(1) 2011, p17-22